Review on recent Developments on Fabrication Techniques of Distributed Feedback (DFB) Based Organic Lasers - Talik N.A.; Kar Y.B.; Tukijan S.N.M.; Wong C.L. (Institute of Physics Publishing, 2023)
Deposition; Distributed feedback lasers; Laser excitation; Nanoimprint lithography; Optical waveguides; Organic lasers; Semiconductor lasers; Corrugated structures; Deposition methods; Distributed feedback; Fabrication method; Fabrication technique; Laser direct writing; Laser interference Lithography (LIL); Photo-excitations; Fabrication